PWE-115 A 13-year, single-centre experience of glucose hydrogen breath testing. (28th May 2012) - Evans, K; Lunn, E; Raza, S; Elphick, D; Sanders, D S
Abstract : Introduction: Historically, the gold standard for diagnosing small intestinal bacterial overgrowth (SIBO) has been quantitative culture of jejunal aspirate. However this test is costly and invasive. More commonly in clinical practice the glucose hydrogen breath test (GHBT) is used. We aimed to determine which clinical features and baseline laboratory investigations indicate a high likelihood of SIBO as defined by positive GHBT. Methods: We undertook a retrospective analysis of records for all patients referred for GHBT at a single teaching hospital over a 13-year period 1998–2010. Data collected included age, sex, baseline and peak hydrogen levels, previous surgical procedures, comorbidities, haemoglobin levels, vitamin B12, folate, ferritin and albumin levels. A positive result was a rise in hydrogen of at least 20 ppm, or methane of 12 ppm, over the baseline for each gas. Results: 447 patients were identified (120 male, median age 56 years, range 17–90). Overall 84/447 (18.8%) of tests were positive. The patient characteristics associated with a positive result were concurrent use of proton pump inhibitor (PPI) (p=0.0005), previous partial gastrectomy (p<0.0001), previous right hemicolectomy (p=0.0004), and age over 75 tears p<0.0001. The laboratory investigations predictive of a positive result were low vitamin B12 (p=0.02) and low albumin <30 g/dl (p=0.03). Conclusion: This is the largest single centre study of factors predictive of SIBO as defined by positive GHBT. Use of proton pump inhibitor, partial gastrectomy, right hemicolectomy, age over 75 years, low vitamin B12 and low albumin were predictive of SIBO. Competing interests: None declared.